2017
DOI: 10.1186/s12978-017-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health experience, knowledge and problems among university students in Ambo, central Ethiopia

Abstract: BackgroundYouths in universities are at high risk of STIs and SRH problems in Ethiopia. However, students did not perceive themselves at risk of STI/HIV infection though reports showed they were sexually active, had multiple sexual partners and reported symptoms of STIs. Having recognized the threat posed by SRH problems, this study aimed to assess the SRH experiences, knowledge, and problems among university students at Ambo University in Ethiopia.MethodsA cross-sectional study was conducted in Ambo Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 2 publications
4
28
0
3
Order By: Relevance
“…In the present study, the majors reasons reported for having premarital sex was fall in love and ful lling sexual desire, and this is in agreement with the nding fromstudents of governmental higher institution in DebreMarkos Town , Ambo University andDebre Tabor University [14,30,41].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the majors reasons reported for having premarital sex was fall in love and ful lling sexual desire, and this is in agreement with the nding fromstudents of governmental higher institution in DebreMarkos Town , Ambo University andDebre Tabor University [14,30,41].…”
Section: Discussionsupporting
confidence: 91%
“…Early pregnancy or marriage accounts for school dropout among an estimated 5% to 33% of girls aged 15 to 24 in some countries [12]. This is also a problem among female students in Ethiopian universities [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no sharp line that discriminates between planned and unplanned pregnancies, pregnancy planning is often measured dichotomously, i.e., planned/unplanned, wanted/unwanted, intended/ unintended and does not take into account that pregnancies may be more or less planned/unplanned (Finer & Kost, 2011;Flower et al, 2013;Singh, Sedgh, & Hussain, 2010;Yared, Sahile, & Mekuria, 2017).…”
Section: • a Comparison Of The London Measurement Of Unplannedmentioning
confidence: 99%
“…Many students perceived SRH to be sexual intercourse and its related consequences, body changes, sexuality and reproduction, marriage, and the use of family planning. Different studies on student perceptions on SRH identi ed that it was all about sexual intercourse and its consequences like STIs, HIV, and pregnancies (33,34). A cross-sectional study among university students in Ethiopia demonstrated that there were minimal reported cases on pregnancies in the quantitative data, but later heavily manifested in the in-depth interviews (34).…”
Section: Discussionmentioning
confidence: 99%